2020
DOI: 10.1177/2042018820938304
|View full text |Cite
|
Sign up to set email alerts
|

Do neuroendocrine carcinomas and mixed neuroendocrine–non-neuroendocrine neoplasm of the gastrointestinal tract have the same prognosis? A SEER database analysis of 12,878 cases

Abstract: Background: Neuroendocrine carcinomas (NECs) and mixed neuroendocrine–non-neuroendocrine neoplasm (MiNEN) in the gastrointestinal (GI) tract are both rare and malignant; however, it is unclear whether their prognosis is the same. Methods: In this cross-sectional study, a total of 12,878 patients with NEC or MiNEN in the GI tract were reviewed retrospectively by searching the Surveillance, Epidemiology, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
17
1
Order By: Relevance
“…Based on our results, the prognosis of GEP MiNEN mirrors that of GEP NEC. A recent study showed that MiNEN has a worse prognosis compared with patients with pure NEC in the small intestine and in the appendix but no statistically significant difference in OS between the two in other parts of the GI-tract [12].…”
Section: Discussionmentioning
confidence: 98%
“…Based on our results, the prognosis of GEP MiNEN mirrors that of GEP NEC. A recent study showed that MiNEN has a worse prognosis compared with patients with pure NEC in the small intestine and in the appendix but no statistically significant difference in OS between the two in other parts of the GI-tract [12].…”
Section: Discussionmentioning
confidence: 98%
“…At present, prognostic factors for NENs are still controversial, and the prognosis depends not only on the stage of the disease but also on the exact histological type [47]. Shi et al considered that the survival time of patients with GB-MiNENs was similar to that of patients with GB-NECs [48]. Harada et al [21] concluded that the presence of the neuroendocrine tumor component of MiNENs in the biliary tract defines the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric MiNENs constitute a small fraction of digestive tumors, most commonly affecting men in their fifth or sixth decade. 4 , 5 The most extensive report on MiNEN trends comes from the Surveillance, Epidemiology, and End Results registry between 1975 and 2016. It reports an incidence of 5.6%, mostly in the appendix, colon, cecum, rectum, or small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…It reports an incidence of 5.6%, mostly in the appendix, colon, cecum, rectum, or small intestine. 5 Compared with other tumors, gastric MiNENs are discovered at advanced stages, and very little is known about them.…”
Section: Discussionmentioning
confidence: 99%